Trastornos psiquiátricos asociados al uso de isotretinoína en el acné severo. Hospital Instituto Ecuatoriano de Seguridad Social. Riobamba, 2014-2019 - Karol Gricel, González Ortega (2022)
ABSTRACT The present work tries to determine a certain relationship between the use of Isotretinoin for the treatment of severe acne and the appearance of psychiatric symptoms in disorders such as depression, anxiety, suicidal thoughts, aggressiveness, among others. To determine the main psychiatric disorders induced by the use of isotretinoin in patients diagnosed with severe acne treated at the Hospital “Instituto Ecuatoriano de Seguridad Social” in Riobamba, during the period January 2014 - December 2019. It is a retrospective, observational and case series study. Patients with a diagnosis of severe acne who attended both Dermatology and Psychiatry outpatient clinics were studied, with a total of 109 people who met the inclusion criteria. In this study it was determined that there is a probable relationship between the use of isotretinoin and the appearance of suicidal ideas reaching a percentage of 51.4 with predominance in the female gender with a total of 38 cases. Regarding the rate of psychiatric disorders presented in this study, it was observed that anxiety was the most frequently expressed pathology after the start of treatment, as was insomnia. However, statistical analysis showed an association between suicidal ideation and isotretinoin in this study. Keywords: Isotretinoin, Dermatology, Psychatry, Anxiety, Suicidal ideation. (DeCS) Firmado electrónicamente por: JHON JAIRO INCA Reviewed by: Lcdo. Jhon Inca Guerrero. ENGLISH PROFESSOR C.C. 0604136572